Bradyarrhythmias in patients with SARS‐CoV‐2 infection: A narrative review and a clinical report. Issue 9 (14th July 2021) - Gatto, Maria Chiara; Persi, Alessandro; Tung, Marzia; Masi, Rosa; Canitano, Stefano; Kol, Amir
Abstract: Several cardiovascular diseases and arrhythmic disorders have been described in COVID‐19 era as likely related to SARS‐CoV‐2 infection. The prognostic relevance of bradyarrhythmias during the infection has not been yet described and no data are available about long‐term heart conduction disorders. A review of literature concerning the association between hypokinetic arrhythmias and COVID‐19 from January 2020 to February 2021 was performed. The key‐words used for the research were: "sinus node disfunction, " "sick sinus syndrome (SSS), " "sino‐atrial block, " "atrio‐ventricular block (AVB), " "bradyarrhythmias, " and "COVID‐19″ or "SARS‐CoV‐2.″ Excluding "relative bradycardia, " a total of 38 cases of bradyarrhythmia related to SARS‐CoV‐2 infection have been described, even in very young people, requiring in many cases a definitive pacemaker implantation. Furthermore, we report a case of non‐hospitalized 47‐years old man with a SSS developed as a consequence of mild SARS‐CoV‐2 infection. While in all described cases heart conduction disorders were found at presentation of the infection or during hospitalization for COVID‐19, in our case the diagnosis of SSS was made after the resolution of the infection. Although rarely, heart conduction disorders may occur during COVID‐19 and the present case highlights that a cardiological follow up may be desirable even after the resolution of infection, especially in the presence of symptoms suggesting a possible heart involvement.